Never again themes and sentiments about the martial law regime under President Ferdinand Marcos as expressed on Twitter - Casem, Elaine T. (School of Library and Information Studies, University of the Philippines Diliman, 2019)
Passing narratives from one generation to another is a common and important human activity. Through this practice, the younger one become aware of the events that happened in the past, even before they were born. However, this kind of practice sometimes cause confusion and misunderstanding among people when there are contradicting claims and narratives. In recent Philippine history, one of the most controversial periods is the Martial Law period under the regime of the late President Ferdinand E. Marcos. Given this, recent events associated to the Marcoses and Martial Law such as how the Marcoses are regaining political prominence, the burial of Ferdinand Marcos at the Libangan ng mga Bayani in 2016, and the proclamation of Martial Law in Mindanao in 2017, brought out reactions and various sentiments from the public particularly in social media platforms. One of these social media site that Filipinos commonly use is Twitter.